Frankie performed the following steps to solve the equation 2m²-24m = -54.

Step 1: 2m² 24m+54 -0

Step 2: 2 (m² - 12m +27) = 0

Step 3: 2 (m-9) (m-3) = 0

Step 4: m-9, -3, 2

Which of the following statements is true?

(1 point)

O Frankie solved the equation correctly.

O Frankie did not perform the correct inverse operation in Step 1.

O Frankie did not factor out the common factor in Step 2.

• Frankie did not factor the trinomial correctly in Step 3.

O Frankie did not find the correct solutions in Step 4.

1 answer

The correct statement is:
• Frankie did not factor the trinomial correctly in Step 3.
Similar Questions
  1. Frankie performed the following steps to solve the equation 2m2−24m=−54. Step 1: 2m2−24m+54=0 Step 2: 2(m2−12m+27)=0
    1. answers icon 1 answer
  2. Frankie performed the following steps to solve the equation 2m2−24m=−54. Step 1: 2m2−24m+54=0 Step 2: 2(m2−12m+27)=0
    1. answers icon 1 answer
  3. Frankie performed the following steps to solve the equation 2m2−24m=−54. Step 1: 2m^2−24m+54=0 Step 2: 2(m^2−12m+27)=0
    1. answers icon 1 answer
  4. Frankie performed the following steps to solve the equation 2m^2−24m=−54Step 1: 2m^2−24m+54=0 Step 2: 2(m^2−12m+27)=0
    1. answers icon 1 answer
more similar questions